INTEGRATED APPROACH AS A METHODOLOGICAL BASIS BUILDING A SOCIAL PACKAGE IN A BUSINESS COMPANY - ZELENA, Mariya; MANTUR-CHUBATA, Olena; DANILKOVA, Anastasiya; SHELEST, Ievgeniia; PETRYCHAK, Viktoria (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article defines the essence of the social package, its structure, approaches to its formation and importance for strengthening the motivation of employees. The theoretical and methodological foundations of the organizational and economic mechanism for determining the integrated approach to building a social package were substantiated, and scientific and applied recommendations for the introduction of an effective employee motivation tool were developed. The social package is defined as a set of financial, material and non-material benefits that raise the standard of living and are provided by the enterprise to the employee in addition to the basic salary in order to encourage labor activity. Four stages of the formation of the social package are distinguished, which replaced each other. Approaches to the definition of the term "social package" in modern literature are defined. A critical analysis of approaches to determining the essence and components of the social package made it possible to single out the commonality of positions regarding the composition of the social package, namely: it should include both the basic social guarantees provided for by the legislation on labor and social security (basic component) and additional material benefits, providing which are carried out by the employer on his own initiative (motivational). The components of the social package are highlighted: mandatory, competitive and compensatory. The most expedient approach to the formation of a social package has been designed.
Keywords: social package; labor motivation; industrial enterprise; labor payment systems; business; business environment